(untitled) (Ciudades, 2018)
This contribution examines the elements associated with the industrial heritage located in the southern districts of the city of Salamanca, beyond the Tormes River, one of the areas of manufacturing location of the capital and whose valuation has rarely been emphasized. To that end, after defining and contextualizing this urban periphery, one must proceed to a characterization and classification of the identified elements and an overview of the tools with which it is wanted and intended to proceed with its recognition, planning and management: a Special Plan and a Strategy for Urban Development.